GENERAL MORPHOLOGICAL SIGNS OF HODGKIN’S LYMPHOMA - Kadamova M. A.; Yuldashev B. S.; Ruzmetov U. A. (Galaxy International Interdisciplinary Research Journal, 2024)
The incidence of Hodgkin’s lymphoma is slightly increased among individuals suffering from severe immunodeficiencies, in particular acquired immunodeficiency syndrome, congenital deficiency of the immune system, and immune disorders asso-ciated with organ transplantation. It should be noted that the degree of this increase is significantly lower than for non-Hodgkin lymphomas.